Micro Structure Analysis of Graphne Oxides from Sawn Waste Synthesis using The Modified Hummer Method - Gina Fadilah NST; - Ramli; Yenni Darvina; Fadhila Ulfa Jhora (Department of Physics – Universitas Negeri Padang UNP, 2023)
The manufacture of graphene oxide material based on sawmill waste charcoal has many applications in the field of technology, one of which is microwave absorption. Sawmill waste as the main ingredient is an effort to improve the processing of abundant sawmill waste. This study aims to analyze the microstructural properties of graphene oxide from sawmill waste synthesized by the modified hummer method. Graphene oxide synthesis was carried out using a modified hummer method which was characterized using a Scanning Electron Microscope (SEM), X-ray Diffraction (XRD ), and Fourier Transform Infrared (FTIR). Based on the results from SEM, the temperatures of 250˚C and 400˚C are perfect graphene oxide blocks. At 300˚C, 350˚C, and 450˚C in the form of sheets. The best results on sem were obtained at 400C with an average diameter of 31.1nm. Based on the results of XRD, it showed a crystal structure in the form of graphene oxide 250˚C, 300˚C, 350˚C, 400˚C, and 450˚C namely Orthorhombic, Cubic, Tetragonal, Hexagonal, and Cubic with the best results at 400˚C where the size The largest average crystal is 53.1 nm. Based on the FTIR results, it contains C, H, and O bonds in the presence of C=O, C=C, O-H, and C-H bonds